Biotechnology and the Mine of Tomorrow. Issue 1 (January 2017) - Dunbar, W. Scott
Abstract : Biotechnology could provide many innovative alternatives for changing the way metals are obtained. Microbes have been used to dissolve metallic minerals and release metal ions into solution, from which pure metal can be obtained by electrolysis. Plants that accumulate metals in their roots and leaves have been used to concentrate metals, and mineral-binding peptides might be used to separate minerals. However, for billions of years microbes have been interacting with metals. Microbial communities in and near mineral sources are therefore a rich source of genetic information which could be used to create synthetic or modified microbiomes that concentrate metals. This would be a complete paradigm-change with enormous scope for transforming the way metals are obtained. Trends: Biotechnology affords possibilities for circumventing or mitigating the constraints on current methods for metal extraction, and could fundamentally change the mining industry. Microbes are used to dissolve sulfide minerals and to treat contaminated water near mines. Ideas for using these and similar microbes to develop different sources of metals are being investigated. Novel uses of biotechnology to detect metals in the earth and to extract metals are an active area of research and development. Efforts to understand the genetic mechanisms of the mineral microbiome are only beginning. Eventually, a set of tools will be developed for modifying a particular mineral microbiome such that metals can be extracted in a natural way.